Pemanfaatan Ubi Jalar Kuning Sebagai Media Alternatif Untuk Pertumbuhan Bibit F0 Jamur Tiram Putih Dan Jamur Merang - Cahya Ningrum, Nunung; , Dra.Hj. Suparti, M.Si (2017)
ABSTRACT Yellow sweet potato can be used as a media for the growth of mycelium mushrooms because it contains many nutrients to grow like carbohydrates, proteins, fats and water. This study have purpose to determine mycelium growth and thickness of mycelium seeds F0 white oyster mushrooms and straw mushroom which is grown on extract media, flour and yellow sweet potato porridge. The method used in this research is the Randomized Complete Design (RAL) experimental factorial pattern consisting of two factors. The first factor is the type of media used in the form of extract, flour and yellow sweet potato porridge and the second factor is the type of fungus used in the form of oyster mushrooms and mushroom. Data analysis using qualitative descriptive. The results showed the fastest growth acceleration of mycelium occurred in medium yellow mushroom yams extract extract with 9 cm long mycelium length and the longest growth occurred on yam mushroom yam oyster mushroom medium with 2.70 cm misellium. While the best mycelium is on and yellow sweet potato purridge media in straw mushroom that is thick. Keywords: mycelium, F0, medium, extract, flour, porridge, yellow sweet potato